A literary-rhetorical analysis of Psalm 93 for translation and performance in isiZulu - Dickie, June F. (Old Testament Essays, 2017)
The proposition underlying this research is that interested isiZulu-speakers could use a systematic methodology to translate selected praise psalms in a poetically-beautiful and rhetorically-powerful way. The methodology has three elements: first the poetic features in the Hebrew text (and their functions) are analysed, using the literary-rhetorical approach of Wendland. Second, for an empirical study, isiZulu-speakers interested in poetry are invited to participate in a workshop to learn the basics of Bible-translation and typical features of Zulu poetry and music. They then compose their own translations of some praise psalms (using Zulu poetic features achieving a similar function to those in the source text) and perform their poems as songs or spoken-poetry items. Third, the success of the exercise is evaluated on the basis of functional translation, using the traditional criteria of accuracy, naturalness, and clarity, as well as the additional criteria of artistry, aurality, and acceptability.
free